"LITTLE WOMAN" BY GRETA GERWIG. SEEN AS A STRATEGY FOR STRENGTHENING STUDENTS' CHARACTER BUILDING - Muhammad Farhan Aulia; Novia Kharina Pakpahan (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
Moral values are universal principles that man views to be good and significant, this research teaches fundamental facts about an ideology that teens can begin to acquire at particular school levels, which can be taught to students through the film Little Women. We found 16 essential moral values from the film and also 12 characters that we can learn from. The data collection technique that is being used is qualitative data collection, The subject in this research is the film itself, "Little Women," which has been adapted from the classic novel by Jane Austen. The subject of this research is the writers as teachers using literature work and transitioning it into teaching material with moral values topic.